Structure determination of atomically controlled crystal architectures grown within single wall carbon nanotubes. - Kirkland, A; Meyer, R; Sloan, J; Hutchison, J (2005)
Indirect high resolution electron microscopy using one of several possible data-set geometries offers advantages over conventional high-resolution imaging in enabling the recovery of the complex wavefunction at the specimen exit plane and simultaneously eliminating the aberrations present in the objective lens. This article discusses results obtained using this method from structures formed by inorganic materials confined within the bores of carbon nanotubes. Such materials are shown to be atomically regulated due to their confinement, leading to integral layer architectures that we have termed "Feynman crystals." These one-dimensional (1D) crystals also show a wide range of structural deviations from the bulk, including unexpected lattice distortions, and in some cases entirely new forms have been observed.